Prevalence, motivation, and outcomes of clinic transfer in a clinical cohort of people living with HIV in North West Province, South Africa - Hannah H. Leslie; Alyssa C. Mooney; Hailey J. Gilmore; Emily Agnew; Jessica S. Grignon; Julia deKadt; Starley B. Shade; Mary Jane Ratlhagana; Jeri Sumitani; Scott Barnhart; Wayne T. Steward; Sheri A. Lippman (BMC Health Services Research, 2022)
Abstract Introduction Continuity of care is an attribute of high-quality health systems and a necessary component of chronic disease management. Assessment of health information systems for HIV care in South Africa has identified substantial rates of clinic transfer, much of it undocumented. Understanding the reasons for changing sources of care and the implications for patient outcomes is important in informing policy responses. Methods In this secondary analysis of the 2014 – 2016 I-Care trial, we examined self-reported changes in source of HIV care among a cohort of individuals living with HIV and in care in North West Province, South Africa. Individuals were enrolled in the study within 1 year of diagnosis; participants completed surveys at 6 and 12 months including items on sources of care. Clinical data were extracted from records at participants’ original clinic for 12 months following enrollment. We assessed frequency and reason for changing clinics and compared the demographics and care outcomes of those changing and not changing source of care. Results Six hundred seventy-five (89.8%) of 752 study participants completed follow-up surveys with information on sources of HIV care; 101 (15%) reported receiving care at a different facility by month 12 of follow-up. The primary reason for changing was mobility (N=78, 77%). Those who changed clinics were more likely to be young adults, non-citizens, and pregnant at time of diagnosis. Self-reported clinic attendance and ART adherence did not differ based on changing clinics. Those on ART not changing clinics reported 0.66 visits more on average than were documented in clinic records. Conclusion At least 1 in 6 participants in HIV care changed clinics within 2 years of diagnosis, mainly driven by mobility; while most appeared lost to follow-up based on records from the original clinic, self-reported visits and adherence were equivalent to those not changing clinics. Routine clinic visits could incorporate questions about care at other locations as well as potential relocation, particularly for younger, pregnant, and non-citizen patients, to support existing efforts to make HIV care records portable and facilitate continuity of care across clinics. Trial registration The original trial was registered with ClinicalTrials.gov , NCT02417233, on 12 December 2014.